An Update on the Management of Hematologic Malignancies in Pregnancy. (May 2014) - Lavi, Noa; Horowitz, Netanel A; Brenner, Benjamin
Hematological malignancies during pregnancy are rare, which results in the absence of large prospective studies. The diagnosis is often delayed due to the symptom similarity to those of pregnancy and the recommendation to avoid imaging studies during gestation. Management of hematological malignancies during pregnancy poses challenges both to the patient and the medical team, given the therapy-attributable risks for mother and fetus and the need to consider patient's preferences regarding pregnancy continuation. Chemotherapy during the first trimester is associated with an increased risk for fetal demise and congenital malformations, while these risks diminish as pregnancy progresses. We hereby present a review of updated literature on the management of hematologic malignancies (Hodgkin and non-Hodgkin lymphomas, acute leukemia, multiple myeloma, chronic myeloid leukemia and myeloproliferative neoplasms) during pregnancy.